Some Results on Core Inverses of Block Matrices Over Skew Fields - Krishnaswamy, D.; Sankari, G. (Communications in Mathematics and Applications, 2022)
In this paper, necessary and sufficient conditions are given for the existence of the core inverse of the block matrix \(pmatrixA&A B&0 pmatrix\) over any skew field, where \(A\), \(B\) are both square and \(rk(B) ≥ rk(A)\). The representation of this core inverse and some relative additive results are also given.